2013
DOI: 10.1007/s00167-013-2441-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental pH change on bovine articular cartilage metabolism: implications for the use of buffered solution during arthroscopy?

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…1 They showed synovial fluid to have a pH of 7.7, a value higher than even blood pH. 1,51 The studies examining pH in this review demonstrated that having a pH close to physiological pH would be ideal 13,27 ; however, it is evident that other properties/factors, such as a solution's ionic make-up, may trump the importance of pH and these other factors would then have to be considered in addition to the solution's pH. A further consideration would be the question of whether a more basic or a more acidic pH would result in greater damage to articular cartilage and should be examined in future studies.…”
Section: Ph Valuesmentioning
confidence: 84%
See 4 more Smart Citations
“…1 They showed synovial fluid to have a pH of 7.7, a value higher than even blood pH. 1,51 The studies examining pH in this review demonstrated that having a pH close to physiological pH would be ideal 13,27 ; however, it is evident that other properties/factors, such as a solution's ionic make-up, may trump the importance of pH and these other factors would then have to be considered in addition to the solution's pH. A further consideration would be the question of whether a more basic or a more acidic pH would result in greater damage to articular cartilage and should be examined in future studies.…”
Section: Ph Valuesmentioning
confidence: 84%
“…Sixteen studies met the inclusion criteria and were included in this review. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] This number is inclusive of the studies found after screening the reference sections of the initial studies ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations